Assessment of pollution with some heavy metals in water, sediments and Barbus xanthopterus fish of the Tigris River–Iraq - Balasim, Halah; Al-Azzawi, Muhammad; Rabee, Adel (Iraqi Journal of Science, 2024)
In this study, four sampling stations were selected on the Tigris River (Baghdad region) in order to determine concentrations, seasonal variation and pollution intensity assessment of heavy metals (Cd, Zn and Mn) in water, sediments and Barbus xanthpterus fish in this river. The study results showed that the mean concentration of dissolved heavy metals (cadmium, zinc and manganese) were 0.004 ppm, 0.023 ppm and 0.007 ppm, respectively. Whereas, their concentrations in sediments were 1.38 ppm, 86 ppm and 231.4 ppm respectively. Irregular seasonal variation for concentrations of these metals in both sediments and water. The mean concentration of these metals in tissues of fish muscles were 0.0043 ppm, 0.0023 ppm and 0.03 ppm for cadmium, zinc, and manganese respectively, while the mean concentration of these metals for tissues of intestine was 0.01 ppm, 0.0023 ppm and 0.029 ppm, respectively, whereas for tissues of gills the mean concentration of these metals was 0.0121 ppm, 0.0026 ppm and 0.087 ppm, respectively. The results of present study showed the metals concentration in tissues of muscles, intestine and gill higher than water and less than it level in sediments. According to Geo-accumulation index, Contamination factor, Enrichment index and potential ecological risk index used in this study the results explained that Cd was more the metals and existing increased in average from background value and caused high risk to aquatic environment, while the use of Pollution load index and Contamination degree to identify to pollution severity by total heavy metals and explained the station one and two were unpolluted to slightly polluted, whereas the station three and four were polluted by studied heavy metals.